2023
DOI: 10.3389/fpls.2022.1102201
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis and expression profiling of potassium transport-related gene families in mango (Mangifera indica) indicate their role in stress response and fruit development

Abstract: Mango (Mangifera indica) fruit is known for its taste, health benefits, and drought tolerance. Potassium (K+) is one of the most abundant ions in a plant cell. It is important for various biological functions related to plant growth, development, and flowering/fruiting. It significantly contributes to fruit yield, quality, and drought tolerance in plants. However, molecular mechanisms comprising K+ transport in mango are least known. In the present study, 37 members of K+ transport-related genes (PTGs) were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…For instance, a study by Tan et al investigated the expression of potassium transporters in the leaves of drought-tolerant cultivar of mango under drought stress. They found that the expression of genes encoding potassium transporters, particularly those involved in the uptake and translocation of potassium such as MiHAK5.2 , MiHAK1.1 , MiTPK2.1 , MiKAT1.1 , and MiAKT6 , was significantly up-regulated [ 68 ]. In addition, genes that regulate flowering in mangoes are implicated in drought tolerance.…”
Section: Omics Approaches To Dissect the Abiotic Stress-resistant Mec...mentioning
confidence: 99%
“…For instance, a study by Tan et al investigated the expression of potassium transporters in the leaves of drought-tolerant cultivar of mango under drought stress. They found that the expression of genes encoding potassium transporters, particularly those involved in the uptake and translocation of potassium such as MiHAK5.2 , MiHAK1.1 , MiTPK2.1 , MiKAT1.1 , and MiAKT6 , was significantly up-regulated [ 68 ]. In addition, genes that regulate flowering in mangoes are implicated in drought tolerance.…”
Section: Omics Approaches To Dissect the Abiotic Stress-resistant Mec...mentioning
confidence: 99%